2010
DOI: 10.1359/jbmr.091031
|View full text |Cite
|
Sign up to set email alerts
|

Vessel formation is induced prior to the appearance of cartilage in BMP-2-mediated heterotopic ossification

Abstract: Heterotopic ossification (HO), or endochondral bone formation at nonskeletal sites, often results from traumatic injury and can lead to devastating consequences. Alternatively, the ability to harness this phenomenon would greatly enhance current orthopedic tools for treating segmental bone defects. Thus, understanding the earliest events in this process potentially would allow us to design more targeted therapies to either block or enhance this process. Using a murine model of HO induced by delivery of adenovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 34 publications
7
72
0
2
Order By: Relevance
“…We previously showed the rapid expansion of new vessels after delivery of the AdBMP-2-transduced cells [7] and in the current study, an extensive vascular plexus can be seen surrounding the claudin 5 + osterix + cells. Furthermore, at the same time, extravasation factors (CXCR4, CD44, and E-selectin) were significantly elevated in these tissues consistent with the appearance, through the circulation, of the cells at this site.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…We previously showed the rapid expansion of new vessels after delivery of the AdBMP-2-transduced cells [7] and in the current study, an extensive vascular plexus can be seen surrounding the claudin 5 + osterix + cells. Furthermore, at the same time, extravasation factors (CXCR4, CD44, and E-selectin) were significantly elevated in these tissues consistent with the appearance, through the circulation, of the cells at this site.…”
Section: Discussionsupporting
confidence: 77%
“…We therefore propose that the exact location of extravasation of the osteoprogenitors is determined by induction of HIF1 in tBAT [27] because of the ability of UCP1 to rapidly generate a hypoxic microenvironment [27]. This process induces vascular endothelial growth factor [7], which then induces new vessel formation. These new vessels are actually the small venules that are required for extravasation [43].…”
Section: Discussionmentioning
confidence: 99%
“…However, MSCs are defined as multipotent cells capable of adipogenic differentiation, and, as such, their contribution to brown adipose tissue formation during the early stages of HO cannot be ruled out. Brown adipocytes formed at the onset of HO have been shown to express vascular endothelial growth factors, concurrent with endothelial progenitor proliferation [43]. Consequently, the presence of brown adipocytes within the lesion reduces the oxygen tension in the adjacent tissue, due to oxidative metabolism [42].…”
Section: Mesoderm Mesenchymal Stem Cellsmentioning
confidence: 99%
“…We then quantified whether this led to new vessel formation, and found a 2 fold enhancement in new vessels in tissues receiving the BMP2 transduced cells (Fouletier-Dilling et al, 2010). We also demonstrated that cells expressing the VEGFs were the brown adipose (Fouletier- Dilling et al, 2010), and that the adipose appears to be generated rapidly, and involved in patterning of the newly forming bone. From these studies we have identified a novel mechanism which shows the molecular pathway induced directly by BMP2, which leads to production of brown adipose, new vessels, peripheral nerve ingrowth, and ultimately cartilage and bone (Olmsted-Davis et al, 2007).…”
Section: B Engineer Cellular Binding Sights Within the Hydrogel To Dmentioning
confidence: 76%